The Metabolic Landscape of Cancer Stem Cells: Insights and Implications for Therapy - Martina Milella; Monica Rutigliano; Savio Domenico Pandolfo; Achille Aveta; Felice Crocetto; Matteo Ferro; Antonio d’Amati; Pasquale Ditonno; Giuseppe Lucarelli; Francesco Lasorsa (Cells)
Cancer stem cells (CSCs) are a subpopulation with self-renewal and differentiation capacities believed to be responsible for tumor initiation, progression, and recurrence. These cells exhibit unique metabolic features that contribute to their stemness and survival in hostile tumor microenvironments. Like non-stem cancer cells, CSCs primarily rely on glycolysis for ATP production, akin to the Warburg effect. However, CSCs also show increased dependence on alternative metabolic pathways, such as oxidative phosphorylation (OXPHOS) and fatty acid metabolism, which provide necessary energy and building blocks for self-renewal and therapy resistance. The metabolic plasticity of CSCs enables them to adapt to fluctuating nutrient availability and hypoxic conditions within the tumor. Recent studies highlight the importance of these metabolic shifts in maintaining the CSC phenotype and promoting cancer progression. The CSC model suggests that a small, metabolically adaptable subpopulation drives tumor growth and therapy resistance. CSCs can switch between glycolysis and mitochondrial metabolism, enhancing their survival under stress and dormant states. Targeting CSC metabolism offers a promising therapeutic strategy; however, their adaptability complicates eradication. A multi-targeted approach addressing various metabolic pathways is essential for effective CSC elimination, underscoring the need for further research into specific CSC markers and mechanisms that distinguish their metabolism from normal stem cells for successful therapeutic intervention.